SEASONAL VARIATION OF PHYTOPLANKTON OF A WATER SYSTEM IN IRAQ - Islam, A K M Sirajul; Khalaf, A N; Al-Jaferi, A R (Indian Journal of Fisheries, 2011)
Seasonal variation of phytoplankton was studied in Rashdiyah reservoir,Baghdad, Iraq, from January to December, 1981. Phytoplankton population showedtwo maxima, first one in M^rch and a second one in November. The total numberof phytoplankton varied between 5 x 10^/1 in March and 0.3 x 10*/l in July.Dry weight of phytoplankton also showed a similar pattern. The overwhelmingmajority of the speciÂ«s were diatoms followed by green and bluegreen algae.Phytoplankton was abundant in spring and autumn followed by winter and summer